Qualidade fisiológica de sementes de Syagrus romanzoffiana (Cham.) Glassman - Magalhães, Thiago Donizetti (2021)
The aim of the present work was to investigate the germination physiology of Syagrus romanzoffiana (Jerivá). The first chapter presents the theoretical framework about the processes and mechanisms intrinsic to germination. In the second, the effect of the harvest period and drying on the seeds of the species, collected in six distinct periods distributed over a year, was evaluated. The effect of the harvest period was observed in all parameters used in the characterization of the species. Seeds collected during the dry season showed superior physiological characteristics compared to those collected during the wet season. Seed drying caused a reduction in germination and seed vigor, and a greater expression of dormancy. The temperature and precipitation variables correlated only with the percentage of germination and dormancy in fresh seed. According to the results, it was possible to conclude that the seeds of S. romanzoffiana present a germination inhibition mechanism that, together with other physiological parameters, presents seasonal variation. In the third chapter, we sought to classify this species as to its storage capacity and to tolerate desiccation. For this purpose, seeds were collected in two different periods, which were subjected to different drying levels. The result of drying and storage was expressed only in percentage of germination. With the lots collected, it was not possible to observe effects of the harvest period on desiccation tolerance. It is inferred that the Romanzoffian has an orthodox behavior.